The Role of Maternal Parenting for Children’s Behavior Regulation in Environments of Risk - Deffaa, Mirjam; Weis, Mirjam; Trommsdorff, Gisela (Frontiers in Psychology, 2020)
This study investigates the role of maternal parenting and subjective theories for associations between environmental risk and children’s behavior regulation combining a qualitative and quantitative approach. Mothers of 113 primary school children (M = 10.06, SD = .86) in Germany completed questionnaires on parenting, environmental risk, and their child’s behavior regulation. To test for associations, we applied hierarchical regression models. Further, we conducted nine focus groups in settings of high and low environmental risk and used thematic analysis. Maternal warmth showed positive associations with children’s behavior regulation. Restrictive maternal control and children’s behavior regulation were related negatively. The negative association between environmental risk and children’s behavior regulation was partly explained by restrictive maternal control. When maternal warmth was added into the model on environmental risk, restrictive maternal control, and children’s behavior regulation, both maternal parenting practices lost its significant associations with children’s behavior regulation. Qualitative findings gave insights into parents’ subjective theories, suggesting adverse peer effects as possible explanation for the relation between environmental risk and children’s behavior regulation. The results are discussed in terms of their contribution to theoretical considerations on behavior regulation development in different environmental risk settings.